The Effect of Regulation, Fintech and Social Media on the Sustainability of the Halal Tourism Industry: An Applied Statistical Analysis Study - Isman, I; Diniyah, Dita Nurul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study examines the impact of regulation, fintech adoption, and social media on the sustainability of halal tourism in Surakarta. The results of the statistical analysis indicate a strong correlation between social media adoption and sustainability, while regulatory support and fintech adoption do not have a significant impact. This study provides original insights by conducting exponential, taxonomic, and componential analyses, which reveal diverse stakeholder interpretations. The article recommends implementing inclusive social media strategies and regulatory support to enhance branding effectiveness. Despite its limitations, this research contributes to policy formulation, fosters collaboration, and enhances the sustainability of halal tourism through a nuanced understanding of regulatory, fintech, and social media influences.